DNA polymerase α-primase can function as a translesion DNA polymerase - Ryan Mayle; Roxana Georgescu; Michael E. O’Donnell (Proceedings of the National Academy of Sciences, 2025)
Replication of cellular chromosomes requires a primase to generate short RNA primers to initiate genomic replication. While bacterial and archaeal primase generate short RNA primers, the eukaryotic primase, Polα-primase, contains both RNA primase and DNA polymerase (Pol) subunits that function together to form a >20 base hybrid RNA–DNA primer. Interestingly, the DNA Pol1 subunit of Polα lacks a 3’-5’ proofreading exonuclease, contrary to the high-fidelity normally associated with DNA replication. However, Polδ and Polε synthesize the majority of the eukaryotic genome, and both contain 3’-5’ exonuclease activity for high fidelity. Nonetheless, even the small amount of DNA produced by Pol1 in each of the many RNA/DNA primers during chromosome replication adds up to tens of millions of nucleotides in a human genome. Thus, it has been a longstanding question why Pol1 lacks a proofreading exonuclease. We show here that Polα is uniquely capable of traversing common oxidized or hydrolyzed template nucleotides and propose that Polα evolved to bypass these common template lesions when they are encountered during chromosome replication. Additionally, we show a unique ability of replication factor C (RFC) to stimulate Polδ lesion bypass, independent of its sliding clamp. This suggests that there may be a coordination between Polδ and RFC that does not involve RFC loading of PCNA.